Seasonal variability in biological trait pattern of biofilm-dwelling protozoa in colonization surveys for marine bioassessment - Gui, Yuying; Bai, Xiaoyun; Zhong, Xiaoxiao; Sikder, Mohammad Nurul Azim; Xu, Henglong (Marine pollution bulletin, 2020)
Biological trait analysis (BTA) has been proved to be a powerful tool to evaluate marine water quality. The species trait distributions of biofilm-dwelling protozoa were studied in a coastal region of the Yellow Sea, northern China, during a four-season cycle. The BTA demonstrated that: (1) the protozoa showed a significant seasonal variability in biological trait pattern during the colonization process across four seasons; (2) the colonization dynamics in species trait distribution followed different temporal models; (3) the functional dynamics in spring and summer were significantly different from those in autumn and winter (P < 0.05); and (4) functional diversity showed lower values in spring and summer than in autumn and winter. These findings suggest that BTA is subject to a high seasonal variability during colonization surveys when protozoa are used as bioindicators of marine water quality. •The protozoa represented a significant seasonal variability in biological trait pattern.•The species trait distribution followed different models in colonization process.•The functional diversity was lower in spring and summer than in autumn and winter.•There was a high seasonal variability in colonization surveys for bioassessment.